Thought Construction of Nasikh Mansukh: Study of Abdullah Ahmad An-Na'im - Rofiq Hidayat (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
Basically, ijtihad is useful in resolving events involving various aspects of human life, especially for answering questions that are not explicitly explained by the texts. One of the contemporary Islamic intellectual figures, particularly in the disciplines of fikih and ushul fikih, is Abdullahi Ahmed An-Na’im. He offers a method of shari’ah evolution (nasakh) which according to him can answer contemporary problems today. This article elaborates on the construction of Abdullah Ahmad An-Na’im’s legal thought. The research uses descriptive-qualitative method, and is included in library research. From the research conducted, it can be seen that 1) Abdullahi Ahmed An-Na’im is more representative of the concept of shari’ah evolution (nasakh) which was initiated by Mahmoud Thaha; 2) An-Na’im with the naskh theory adopted from his teacher wants to say that the verse that is used as the basis of Islamic law at this time is revoked and replaced with an erased verse to be used as the basis of modern Islamic law, because of its more universal nature.